Characterization of pseudobasophilia on Sysmex-XT 1800i automated hematology analyser - Mannem, Chethana; Krishanmurthy, Thejasvi; Gayathri B. R., Gayathri; Prabhu, Preetha D. (International Journal of Research in Medical Sciences, 2017)
Background: Pseudobasophilia is a common automation related phenomenon which requires manual peripheral smear study in an era of complete automation. This study has attempted to evaluate the reasons for pseudobasophilia and in-turn suggest measures to eliminate the errors. Methods: A sample size of 207 cases showing pseudobasophilia on automation were studied by manual peripheral examination to categorize the possible cause for its occurrence. Descriptive and inferential statistical analysis was carried out. Results on continuous measurements are presented on Mean SD and results on categorical measurements are presented in Number (%). Significance is assessed at 5% level of significance. Student t test has been used to find the significance of study parameters on continuous scale within each group. Results: Atypical/ reactive lymphocytes were present in 86.5% cases contributing to pseudobasophilia phenomenon on automation, which also showed falsely increased absolute basophil count with more percentage of lymphocytes showing reactive changes. Temperature and storage effects did not contribute to their occurrence in this study. Another finding was an associated pseudomonocytosis with pseudobasophilia on automation which was statistically significant (p<0.001). Conclusions: Pseudobasophilia, and pseudomonocytosis are automation related phenomenon. Atypical/ reactive lymphocytes, which are cytoplasmic strip resistant, contribute to their occurrence. Hence, newer modalities like multicolour flow cytometry coupled with antibody tagging, multiangle polarised scatter separation and volume conductivity scatter may reduce the chances of pseudobasophilia, thereby reducing the overall turnaround time.